KAIDAH FIQH BIDANG MU’AMALAH MAZHAB SYAFI’I (Kajian Teoritis dan Praktik serta Kehujjahannya) - Sumarjoko Sumarjoko; Hidayatun Ulfa (Jurnal Iqtisad, 2019)
Abstract The Islamic economic system is believed to be the way of salvation. This will replace the capitalist and socialist economic systems which are considered to be unable to provide a sense of justice and prosperity. To meet and answer the challenge, Islamic jurists (fuqaha) in various layers carried out a methodological study of Islamic law, critical of the manhaj (method) that classical scholars have formulated. The jurists acknowledged, that, legal texts were limited, while new legal cases were constantly developing "An-nushus mutanahiyah wa al-waqa‟u ghairu mutanahiyah". On this matter, it is necessary to develop a method (manhaj al-ijtihad) seriously by legal experts, practitioners or shari'ah economists in solving problems related to mu'amalah. For this reason, ushul fiqh is a procedure of ijtihad as well as a barometer of the jurisprudence of a law. At its climax, ushul fiqh from the beginning to being a formulation of Islamic law continues to get attention related to the principles of general argument. Then created the formulation of al-qawaid al-ushuliyyah and al-qawaid alfiqiyyah. The rule of fiqh is a science that helps mechanically in furu problems. The rules of fiqh are also formulated as a simplifier in the problem of furu ' or fiqiyyah. In literacy of Islamic law, between usul rules and fiqh rules sometimes occur intermingling. Sometimes the rules of usul are not separated in the same discussion with the rules of fiqh, but each has its own limits and reach. Ushul rules in its application as “Takhrij al-Ahkam” (issuing law from its source), while the fiqh rule is “Tathbiq alAhkam” which applies to cases that arise in human life. The jurisprudence of the rules of fiqh occurred in the Syafi'ah school of khilafiyyah. Nevertheless, it can be classified with the following provisions: first, if the fiqh rule is general (kulli), it can be used as a source of law as nash, ijma and qiyas. Its existence is very significant and can make the argument or proof of matter. Second, if the rule is a majority (aghlabiyah) then it is disputed. On this basis, this study is very important to be further explored. Keyword: Kaidah fikih, muamalah, kehujjahan Abstrak Sistem ekonomi Islam diyakini sebagai jalan keselamatan. Ini akan menggantikan sistem ekonomi kapitalis dan sosialis yang tidak mampu memberikan rasa keadilan dan kemakmuran. Untuk memenuhi dan menjawab tantangan tersebut, para ahli hukum Islam (fuqaha) di berbagai lapisan dilakukan studi metodologis hukum Islam, kritis terhadap manhaj (metode) yang telah dirumuskan para ulama klasik. Para ahli hukum mengakui, bahwa, teks-teks hukum terbatas, sementara kasus-kasus hukum baru terus berkembang "An-Nushus Mutanahiyah wa al-waqa'u ghairu mutanahiyah". Dalam Jurnal Iqtisad: Reconstruction of Justice and Welfare for Indonesia – Vol. 6, No 1 (2019) p-ISSN: 2303-3223; e-ISSN: 2621-640X Kaidah Fiqh Bidang Mu’amalah.... 33 Sumarjoko, Hidayatun Ulfa hal ini, ini adalah metode (manhaj al-ijtihad) yang serius oleh para ahli hukum, praktisi atau ekonom syariah dalam menyelesaikan masalah yang berkaitan dengan mu'amalah. Untuk alasan ini, usul fiqh adalah prosedur ijtihad serta barometer yurisprudensi hukum. Pada klimaksnya, ushul fiqh terkait dengan prinsip-prinsip argumen umum. Kemudian dibuat rumusan al-qawaid al-ushuliyyah dan al-qawaid alfiqiyyah. Aturan fiqh adalah ilmu yang membantu secara mekanis dalam masalah furu. Aturan fiqh juga dirumuskan sebagai penyederhanaan dalam masalah furu' atau fiqhiyyah. Dalam literasi hukum Islam, antara aturan proposal dan aturan fiqh terkadang terjadi pembauran. Terkadang aturan proposal tidak dipisahkan dalam diskusi yang sama dengan aturan fiqh, tetapi masing-masing memiliki batas dan jangkauannya sendiri. Aturan Ushul dalam penerapannya sebagai "Takhrij al-Ahkam" (mengeluarkan hukum dari sumbernya), sedangkan aturan fikih adalah "Tathbiq al-Ahkam" yang berlaku untuk kasus-kasus yang muncul dalam kehidupan manusia. Yurisprudensi aturan fiqh di sekolah Syafi'ah khilafiyyah. Namun demikian, ini dapat digunakan sebagai sumber hukum seperti nash, ijma dan qiyas, pertama, jika aturan fiqh bersifat umum (kulli). Keberadaannya sangat signifikan dan bisa dijadikan argumen atau pembuktian materi. Kedua, jika aturannya adalah mayoritas (aghlabiyah) maka itu diperdebatkan. Atas dasar ini, penelitian ini sangat penting untuk dieksplorasi lebih lanjut. Kata kunci: Aturan fikih, muamalah, kehujjahan